REMISSION FOR CORRUPTORS AND THE CHALLENGES OF THE CORRUPTION ERADICATION IN INDONESIA - Munandar (FH 16 UMY 078, 2016)
Granting of remission for prisoners has been set in the Correctional Act 1995 (UU No. 12 Tahun 1995 Tentang Pemasyarakatan) and granting remission for corruptors has been set specifically in Government Regulation on the second amendment of Government Regulation No. 99 of 2012 on the requirements and procedures for the implementation of the rights of prisoners. Eventhough the law justifies the granting of remission for corruptors, this policy will injure the public’s sense of justice. It is because the corruption is harmfull for the society. From the point of view of human rights corruption has been recognized as the violation of social and economic rights of the people. Therefore, corruption should no longer be classified as an ordinary crime, but extraordinary crime. The penalty for corruptors commonly tends to be mild at this time, especially due to the granting of remission. The paper aims to discuss the policy of granting remission for corruptors based in the philosophical, sociological, historical and juridical views. By using the normative qualitative method, the research found that in this policy has the challenges in corruption eradication in Indonesia, it is because this policy is contrary with the spirit of the government in corruption eradication In Indonesia and remission will remove the objective of sentencing. Keywords: coruption, challenges, policy, remission.